Pelatihan Perilaku Hidup Bersih dan Sehat (PHBS) dalam Upaya Perubahan Perilaku Cuci Tangan Pakai Sabun (CTPS) pada Siswa di SDN Maumbi dan SDN Inpres Watutumou Kabupaten Minahasa Utara - Dismo Katiandagho; Jusran Mokoginta; Anselmus Kabuhung (CV. CENDIKIA JENIUS INDONESIA, 2024)
Clean and healthy living behavior (PHBS) is defined as behavior that is practiced with awareness as a result of learning and the realization of a healthy paradigm that makes individuals and families healthy. The aim of this service is to find out the extent to which PHBS is implemented in school settings with the habit of washing hands with coconut fiber among students at SDN Maumbi and SDN Inpres Watutumou, North Minahasa Regency. Service activity method This method of implementing community service is carried out by conducting an initial survey at the location where community service activities will be carried out, approaching the school and registering data on all students. The intervention provided was the creation of hand washing stations for students and teachers. The results of the activity show the realization of 4 units/set of hand washing facilities which are ready for use by students and teachers at SDN Maumbi and SDN Inpres Watutumou, each with 2 units/set of hand washing facilities. Conclusion: the target of preventing COVID-19 was achieved, by changing the behavior of students by washing their hands with soap independently at school and at home.